2017
DOI: 10.1093/nar/gkx550
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between histone modifications indicates that inhibition of arginine methyltransferase CARM1 activity reverses HIV latency

Abstract: In eukaryotic cells, the gene expression status is strictly controlled by epigenetic modifications on chromatin. The repressive status of chromatin largely contributes to HIV latency. Studies have shown that modification of histone H3K27 acts as a key molecular switch for activation or suppression of many cellular genes. In this study, we found that K27-acetylated histone H3 specifically recruited Super Elongation Complex (SEC), the transcriptional elongation complex essential for HIV-1 long terminal repeat (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 62 publications
2
45
0
Order By: Relevance
“…Although we have long understood the positive feedback loop mechanism driven by Tat [38], we lack knowledge of mechanisms that actively silence the provirus. However, recent studies have revealed negative HIV-1 feedback loops that might rely on RNA precursor export [58] or histone modifications through the arginine methyltransferase CARM1 [59]. Interestingly, H3K27ac promotes CARM1-mediated HIV-1 latency.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have long understood the positive feedback loop mechanism driven by Tat [38], we lack knowledge of mechanisms that actively silence the provirus. However, recent studies have revealed negative HIV-1 feedback loops that might rely on RNA precursor export [58] or histone modifications through the arginine methyltransferase CARM1 [59]. Interestingly, H3K27ac promotes CARM1-mediated HIV-1 latency.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that H3R26 methylation represses transcription through inhibiting the binding of the Super Elongation Complex (SEC) with H3K27ac, an active transcription mark (Zhang et al, 2017). Thus, the two marks generated by CARM1 can be active or repressive depending on relative levels of each modification.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during latency, the HIV-1 promoter is heavily controlled by epigenetic mechanisms, including DNA methylation (Blazkova et al, 2009;Kauder et al, 2009;Chávez et al, 2011) and histone post-translational modifications, such as histone acetylation (Lusic et al, 2003;Jiang et al, 2007;Tyagi and Karn, 2007;Li et al, 2018), methylation (du Chéné et al, 2007Marban et al, 2007;Imai et al, 2010;Friedman et al, 2011;Ding et al, 2013;Tchasovnikarova et al, 2015Tchasovnikarova et al, , 2017Boehm et al, 2017;Nguyen et al, 2017;Zhang et al, 2017;Huang et al, 2019), and crotonylation (Jiang et al, 2018). The degree of DNA methylation on the HIV-1 promoter was long considered controversial due to conflicting observations in patients (Blazkova et al, 2009(Blazkova et al, , 2012Kauder et al, 2009;Ho et al, 2013;Weber et al, 2014).…”
Section: Complexity Of Molecular Mechanisms Regulating Hiv-1 Latencymentioning
confidence: 99%